An audit of initial six years of 5885 telepsychiatric direct video consultations: Findings from “benefits of savings” analysis and the effect of COVID-19 pandemic - James Paul; Radhakrishnan Govindan; Poreddi Vijayalakshmi; B. V. Kathyayani; Sailaxmi Gandhi; Rajendra K. Madegowda; Chethan Basavarajappa; Narayana Manjunatha; C Naveen Kumar; Suresh Bada Math (Indian Journal of Psychiatry)
Background: Telepsychiatric direct video consultations (DVCs) meant for continuity of care began in 2017 and continued during the coronavirus disease 2019 (COVID-19) pandemic. Telemedicine-based consultation gained its long-due importance during the COVID-19 travel restriction, despite its existence for a long. The authors intend to share the utility and growth of the initial six years of live telepsychiatric DVCs from an academic hospital in India and also plan to understand the effects of the COVID-19 pandemic on its growth and report findings from an innovative “benefits of savings” (BOS) analysis from these clinics. Methods: A first six years of medical audit of the files and registers of telepsychiatric DVCs from two kinds of continuity of care clinics during 2017–2022 is performed. An analysis of 4991 (84.8%) live DVCs is successfully conducted for 1570 patients from the 5885 scheduled appointments. Year-on-year (YOY) growth and BOS analysis of successful DVCs from these clinics were performed. Results and Discussion: The growth suggests a gradual increase in DVCs yearly. The BOS analysis suggests its increased acceptability, feasibility at both user and provider ends, and possible cost-effectiveness of these video clinics. YOY analysis suggests a natural growth of these clinics than from the effect of the COVID-19 pandemic, except for an initial surge in 2020 and 2021 and observing stabilization effect by 2022. Conclusion: In the authors’ understanding, this is the largest study of providing DVCs from India, irrespective of any medical/surgical specialty. The video/remote clinics could be an alternative model for regular follow-ups in ensuring the continuity of care among patients with psychiatric disorders. These clinics also saved significant travel time, travel distance, and travel costs for the patients that could have occurred for their in-person consultations.